Advances in Computational Biology - Arabnia, Hamid R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Proceedings of The 2009 International Conference on Bioinformatics and Computational Biology in Las Vegas, NV, July 13-16, 2009. Recent advances in Computational Biology are covered through a variety of topics. Both inward research (core areas of computational biology and computer science) and outward research (multi-disciplinary, Inter-disciplinary, and applications) will be covered during the conferences. These include: Gene regulation, Gene expression databases, Gene pattern discovery and identification, Genetic network modeling and inference, Gene expression analysis, RNA and DNA structure and sequencing, Biomedical engineering, Microarrays, Molecular sequence and structure databases, Molecular dynamics and simulation, Molecular sequence classification, alignment and assembly, Image processing In medicine and biological sciences, Sequence analysis and alignment, Informatics and Statistics in Biopharmaceutical Research, Software tools for computational biology and bioinformatics, Comparative genomics; and more.
Part I: Bioinformatics Databases, Data Mining, and Pattern Discovery -- A Classification Method Based on Similarity Measures of Generalized Fuzzy Numbers in Building Expert System for Postoperative Patients by Pasi Luukka -- Efficient Support Vector Machine Method for Survival Prediction with SEER Data by Zhenqiu Liu, Dechang Chen, Guoliang Tian, Man-Lai Tang, Ming Tan, and Li Sheng -- Searching Maximal Degenerate Motifs Guided by a Compact Suffix Tree by Hongshan Jiang, Ying Zhao, Wenguang Chen, Weimin Zheng -- Exploring Motif Composition of Eukaryotic Promoter Regions by Nikola Stojanovic, Abanish Singh -- Large-Scale Analysis of Phylogenetic Search Behavior by Hyun Jung Park, Seung-Jin Sul, and Tiffani L. Williams -- Silicosection and Elucidation of the Plant Circadian Clock Using Bayesian Classifiers and New Genemining Algorithm by Sandra Smieszek, Rainer Richter, Bartlomiej Przychodzen, Jaroslaw Maciejewski -- ChemBrowser: A Flexible Framework for Mining Chemical Documents by Xian Wu, Li Zhang, Ying Chen, James Rhodes, Thomas D Griffin, Stephen K Boyer, Alfredo Alba, Keke Cai.-Experimental Study of Modified Voting Algorithm for Planted (l,d)-Motif Problem by Hazem M Bahig, Mostafa M Abbas, and Ashraf Bhery -- Prediction of Severe Sepsis Using SVM Model by Shu-Li Wang, Fan Wu, Bo-Hang, Wang -- Online Multi-Divisive Hierarchical Clustering for On-body Sensor Data by Ibrahim Musa Ishag Musa, Anour F.A. Dafa-Alla, Gyeong Min Yi, Dong Gyu Lee, Myeong-Chan Cho, Jang-Whan Bae, and Keun Ho Ryu -- On Quality Assurance and Assessment of Biological Datasets and Related Statistics by Maria Vardaki and Haralambos Papageorgiou -- Pattern Recognition Informed Feedback for Nanopore Detector Cheminformatics by A. Murat Eren, Iftekhar Amin, Amanda Alba, Eric Morales, Alexander Stoyanov, Stephen Winters-Hilt -- A MLP Neural Network for ECG Noise Removal Based on Kalman Filter by Sara Moein -- Discovery of Structural Motifs Using Protein Structural Alphabets and 1D Motif-finding Methods by Shih-Yen Ku, Yuh-Jyh Hu -- Biological databases at DNA Data Bank of Japan in the era of next-generation sequencing technologies by Yuichi Kodama, Eli Kaminuma, Satoshi Saruhashi, Kazuho Ikeo, Hideaki Sugawara, Yoshio Tateno and Yasukazu Nakamura -- Part II: Microarray, Gene Expression Analysis, and Gene Regulatory Networks -- Comparison of Microarray Pre-Processing Methods by Kabita Shakya, Heather J. Ruskin, Grainne Kerr, Martin Crane, Jeremie Becker -- A Robust Ensemble Classification Method for Microarray Data Analysis by Zhongwei Zhang, Jiuyong Li, Hong Hu, Hong Zhou -- k-NN for the Classification of Human Cancer Samples using the Gene Expression Profiles by Manuel Martin-Merino -- The Application of Regular Expression Based Pattern Matching to Profiling the Developmental Factors that Contribute to the Development of the Inner Ear by Christopher M. Frenz & Dorothy A. Frenz -- Functionally Informative Tag SNP Prioritization Using a Pareto-Optimal Approach by Phil Hyoun Lee, Jae-Yoon Jung, and Hagit Shatkay -- KMeans-Greedy Search Hybrid Algorithm for Biclustering Gene Expression Data by Shyama Das and Sumam Mary Idicula -- Robust Stability Analysis and Design Under Consideration of Multiple Feedback Loops of the Tryptophan Regulatory Network of E.Coli by A. meyer-Baese, F. Theis and M. Emmett -- FM-GA and CM-GA for Gene Microarray Analysis by Lily R. Liang, Rommel A. Benites Palomino, Zhao Lu, Vinay Mandal, Deepak Kumar -- Part III: Protein Classification and Structure Prediction, and Computational Structural Biology -- Novel Features for Automated Cell Phenotype Image Classification by Loris Nanni, Sheryl Brahnam, Alessandra Lumini -- A Relational Fuzzy C-Means Algorithm for Detecting Protein Spots in Two-Dimensional Gel Images by Shaheera Rashwan, Talaat Faheem, Amany Sarhan, Bayumy A.B.Youssef -- Assigning Probabilities to Mascot Peptide Identification Using Logistic Regression by Jinhong Shi and Fang-Xiang Wu -- Genome-Wide EST Data Mining Approaches to Resolving Incongrue.
Keywords: Medicine; Bioinformatics; Biological models; Biomedicine; Bioinformatics; Computational Biology/Bioinformatics.; Systems Biology